2018
DOI: 10.1377/hlthaff.2017.1173
|View full text |Cite
|
Sign up to set email alerts
|

Health Departments With A Commitment To Health Equity: A More Skilled Workforce And Higher-Quality Collaborations

Abstract: Health equity is a public health priority, yet little is known about commitment to health equity in health departments, especially among chronic disease prevention practitioners whose work places them at the forefront of addressing the top contributors to disparities in morbidity and mortality. A random sample of state chronic disease practitioners (N=537) was surveyed on health equity commitments, partnerships, and needed skills. A small percent of respondents worked primarily on health equity (2%) and more (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Our findings also build upon past research on crosssector collaboration, which are instrumental in reducing preventable deaths attributable to chronic disease [31,32]. Ameliorating health inequities requires a multisystemic approach [33,34]. We found that in HHI crosssector collaboration was largely accomplished through coalition work.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our findings also build upon past research on crosssector collaboration, which are instrumental in reducing preventable deaths attributable to chronic disease [31,32]. Ameliorating health inequities requires a multisystemic approach [33,34]. We found that in HHI crosssector collaboration was largely accomplished through coalition work.…”
Section: Discussionsupporting
confidence: 73%
“…The socio-ecological model informed program development, shaped evaluation questions and metrics, and encouraged community partners see how policy, system, and environment affected community health [30]. Cross-sector collaboration was used [31,32,33,34]. In this, communty partners were encouraged to use the socio-ecological model, and to focus on the outer rings of it.…”
Section: Resultsmentioning
confidence: 99%
“…NACDD is a professional organization dedicated to improving "the health of the public by strengthening state-based leadership and expertise for chronic disease prevention and control in states and at the national level" within the United States [38]. In 2015, a national survey was conducted of state chronic disease directors and state chronic disease prevention and health promotion program staff who were members of the National Association of Chronic Disease Directors [31,39]. States were ranked by overall capacity in EBPH using participants' responses to items in the national survey about the use of EBDM in their health department, public health accreditation status (accreditation indicating higher capacity), and the preventable burden of disease in each state.…”
Section: State Site Selectionmentioning
confidence: 99%
“…Prior work has described the important role of the public health system in general and health departments in particular on intervening to reduce health inequities, which Liburd et al describe as part of a three-way linkage between practice, policy and research [ 17 ]. The current study complements other studies that have examined the capacity of health departments to engage in health equity-related work that have been either qualitative in nature [ 25 ], have focused on other aspects of capacity [ 26 28 ], examined state rather than local settings [ 29 ], or require high levels of resources and commitment [ 21 ].…”
Section: Discussionmentioning
confidence: 85%